Artificial Intelligence and Gender in South Asia: A Review - Gosain, Ashish (Journal of Data Science, Informetrics, and Citation Studies, 2026)
UNESCO Women for Ethical AI: Outlook Study on Artificial Intelligence and Gender in South Asia. UNESCO, New Delhi, 2026, available online at https://unesdoc.unesco.org/
Keywords: AI Ethics; AI Governance; AI Leadership; Gender and AI; Global South; South Asia